Brave New World for University Educators : Effects of Pedagogical Training on Teaching at Higher Education Level - Norazila, Abd Aziz; Hong, Kian Sam; Fitri Suraya, Mohamad; Peter, Songan; Gabriel Tonga, Noweg (2007)
Mastery of content knowledge and expertise in research are no longer the only requirements expected of university educators. Knowledge of a range of pedagogical skills is also elemental to ensure effective delivery of instruction, enabling meaningful transfer of knowledge takes place. Recognizing the need to develop and upgrade its academics’ pedagogical knowledge and skills, Universiti Malaysia Sarawak (UNIMAS), in 2002, initiated a Postgraduate Diploma in Teaching and Learning program (PGDip in TL) with the objectives of developing and enhancing its academics’ knowledge, competence and performance in teaching. This paper presents the findings of a study which investigated the effects of pedagogical training, specifically the PGDip in TL program on UNIMAS’ academics approaches to teaching. Implication of the findings on the design and development of pedagogical training modules for university educators is also addressed.